Woodfordia fruticosa (L.) Kurz: An Evidence-based Study of its Phytochemical and Pharmacological Activities - Singh, Kuldeep; Gupta, Jeetendra Kumar; Pathak, Devender; Kumar, Shivendra; Srivastava, Ateet; Mishra, Avinash Kumar; Patel, Aman; Prajapati, Harshit (Current Traditional Medicine, 2025)
Woodfordia fruticosa (L.) Kurz, a member of the 'Lythraceae' family, has been used in traditional medicine to cure common diseases since ancient times. It is traditionally used to treat a variety of maladies such as the common cold, toothache, blood infection, leprosy, dysentery, wounds, rheumatic pain, fever, urinary issues, inflammation, infertility, and menstrual problems. The huge potential and impacts of this plant have been thoroughly confirmed in in vitro and in vivo studies. The most current research on the plant Woodfordia fruticosa is critical for identifying the bioactive components responsible for its medicinal efficacy. Phytochemical studies reveal the existence of several chemicals extracted from various components of the plant, including glycosides, terpenes, flavonoids, tannins, sterols, phenolics, and essential oils. According to pharmacological studies, the plant has many medicinal properties, such as hypoglycemic, antioxidant, analgesic, hepatoprotective, antibacterial, gastroprotective, and wound healing. Most of the pharmacological effects of raw extracts of this plant have been described. Only a few researchers have reported the activity of chemicals isolated from this plant. Therefore, this research will help to discover the many different medicinal properties of the plant as well as its pharmacological effects on various diseases and will show that further research is needed to explore its practical applications.
Keywords: wound healing